Polish ethnopolitical myth and the Caucasus : Looking at the past - Adamczewski, Przemysław (Iran and the Caucasus Monographs, 2026)
Does the fact that we dislike someone influence our perception of the world? If Poles consider Russians as "historical" enemies, does this affect how they interpret the present and the past? The author argues this is indeed the case. In his book, the author illustrates this through the example of the Caucasus, primarily in the context of the nineteenth century, when the modern Polish nation was being formed. How did the Polish independence emigration view the independence struggles of the Caucasian peoples? And how do contemporary Polish researchers and publicists approach the issue? Where does Russia fit into all of this? The author seeks to answer these and many other questions in his account about an imagined Polish-Caucasian comradery.